Self-efficacy and Adaptive Performance of Head Nurses in Affiliated Hospitals of Dali University, People’s Republic of China - Zhang , Yunhong; Nantsupawat, Apiradee; Thungjaroenkul , Petsunee (Nursing Journal CMU, 2021)
Self-efficacy and adaptive performance are important components in the healthcare system for reaching positive organizational outcomes. However, little is known about the relationship between self-efficacy and adaptive performance. The purpose of this descriptive correlation study was to examine the self-efficacy and adaptive performance of head nurses, as well as to explore the relationship between self-efficacy and adaptive performance of head nurses in the affiliated hospitals of Dali University, the People’s Republic of China. The participants consisted of 135 head nurses from four affiliated hospitals in Yunnan Province. The instruments included the General Self-Efficacy Scale (GSES) developed by Zhang & Schwarzer (1995) and the Adaptive Performance Scale developed by Charbonnier-Voirin & Roussel (2012). The Adaptive Performance Scale was translated into Chinese by the researcher without modification. The validity of GSES and Adaptive Performance Scale were confirmed. The Cronbach’s alpha coefficients of GSES and Adaptive Performance Scale were .86 and .89. Data were analyzed using descriptive statistics and Pearson product-moment correlation. The results of this study revealed that the mean score of self-efficacy of head nurses was 2.81 (SD= 0.49), lower than the international norm value of 2.9. The adaptive performance of head nurses was at a high level (=5.59, SD= 0.56). Self-efficacy of head nurses had a moderate positive correlation with adaptive performance (r= .50, p<.01). The results of this study provide basic information and knowledge for hospital administrators to develop hospital policy and management strategies to increase head nurses’ self-efficacy, which will enhance their adaptive performance.